Phytochemical Screening and in Vitro Ovicidal, Larvacidal, and Nematicidal Effects of Murraya paniculata (L.) Jack Extract on Gastrointestinal Parasites of Goats - G. E. Tresia; D. Evvyernie; R. Tiuria (Media Peternakan, 2016)
In our previous research, kemuning leaves (Murraya paniculata L. Jack) was shown to have the capability as an anthelmintic candidate for PE (Ettawa crossbred) lactating dairy goats by reducing 43.67% of the egg per gram (EPG) of Strongylida compared to 0.0005% in orally treated with Oxfendazole as a control. To confirm it, the aim of this in vitro study was to determine the effective dosage of kemuning leaves from two extraction methods (infuse and maceration) to reduce the Trichostrongylidae and to evaluate the bioactive compounds of the leaves. The research was conducted using a randomized complete design with 11 treatments and 5 replications. The treatments consisted of control (0.0005% and 0.005% Oxfendazole), kemuning leaves infuse extract (KIE) and maceration extract (KME) each with level of 1%, 3%, 5%, and 7% (w/v). The results showed that the LT50 gradually decreased (shortening the lethal time) and the mortality of Trichostrongylidae gradually increased associated with the increased concentration of treatment (P<0.01). The infusion of 7% kemuning extract demonstrated the highest efficiency in reducing the larval development, infective larvae, and the adult Trichostrongylidae by 93.16%, 94.39%, and 90%, respectively.  This treatment could be developed as the most prospective herbal anthelmintic drug in controlling the infection by Trichostrongylidae.